2005
DOI: 10.1111/j.1471-0528.2005.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

General gynaecology: Intrauterine lignocaine as an anaesthetic during endometrial sampling: a randomised double‐blind controlled trial

Abstract: Objective To evaluate the effectiveness of intrauterine lignocaine as an anaesthetic during endometrial sampling.Design Prospective, randomised, double-blind, placebo-controlled trial.Setting Outpatient gynaecological minor operation unit in a public hospital.Population Two hundred premenopausal women scheduled for endometrial sampling because of abnormal uterine bleeding.Methods Transcervical intrauterine instillation of 5 mL of 2% lignocaine or 5 mL of normal saline before performing endometrial sampling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…(Table 1) Four studies involved biopsy with a biopsy cannula,(1518) two used biopsy with a vacuum aspirator,(19, 20) and two reported on curettage with a sharp Sims curette. (21, 22) All studies used a saline placebo comparator.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1) Four studies involved biopsy with a biopsy cannula,(1518) two used biopsy with a vacuum aspirator,(19, 20) and two reported on curettage with a sharp Sims curette. (21, 22) All studies used a saline placebo comparator.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Pipelle procedure is more comfortable than dilation and curettage, patients may still suffer from discomfort and pain. Several pain-reduction methods have been evaluated in the literature; for example, intrauterine anesthesia, intrauterine anesthesia plus a nonsteroidal anti-inflammatory drug (NSAID), topical analgesia, intrauterine anesthesia plus buccal misoprostol, and transcutaneous electrical nerve stimulation have been tested [5,6,7,8,9,10,11]. The local benzocaine study was the only study that did not demonstrate pain reduction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al ., randomized, double-blind, placebo-controlled trial found the intrauterine instillation of lignocaine reduced pain during endometrial sampling. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%